Screening for iron deficiency among pregnant women - Wejdan S. AlQurashi; Reham A. Abdulgader; Rawan A. Gari; Maha A. Badawi (npj Women's Health)
Abstract Iron deficiency (ID) and iron deficiency anemia (IDA) are extremely common in females in Saudi Arabia and are highly prevalent in pregnancy. The Saudi MOH Mother Health Passport recommends that pregnant women undergo testing for complete blood count and ferritin in every trimester. The purpose of this study was to describe practices of screening pregnant women for ID or IDA during pregnancy and to identify the prevalence of anemia and IDA. The inclusion criteria were all patients who had at least 2 antenatal visits in the same center and 336 women were included. It was noted that 591 (51.5%) hemoglobin tests were performed during pregnancy, a 50% gap in comparison with MOH recommendations of measuring Hb in every trimester. The overall prevalence of anemia was 28.6%, 12.2% in the first trimester, 37.2% in the second trimester, and 36.3% in the third trimester. Ferritin was measured in less than 5% of patients, and most women had ferritin levels below 15 ng/ml. Screening practices for IDA and ID among pregnant women are suboptimal, and the prevalence of both entities is substantial. The development of detailed national guidelines for screening and managing ID and IDA in pregnancy is recommended.